Educational Delusions? : Why Choice Can Deepen Inequality and How to Make Schools Fair. - Orfield, Gary (Staff and educational development series., 2012)
The first major battle over school choice came out of struggles over equalizing and integrating schools in the civil rights era, when it became apparent that choice could be either a serious barrier or a significant tool for reaching these goals. The second large and continuing movement for choice was part of the very different anti-government, individualistic, market-based movement of a more conservative period in which many of the lessons of that earlier period were forgotten, though choice was once again presented as the answer to racial inequality. This book brings civil rights back into.